A simple circuit to improve the power yield of PV array during partial shading - Salam, Zainal; Ramli, Mohd zulkifli (2012)
In a typical photovoltaic (PV) power system, when part of the PV module is shaded, the bypass diode is activated to protect the module from hot-spot damages. As a result, the output power is reduced significantly because the power generated from the shaded module is totally unusable. In this paper, a simple circuit is proposed to increase the power yield of PV system under partial shading condition. The idea is to recover the power generated by the shaded module and then process it using power electronics circuit to become part of the output power. Consequently, the inclusion of the circuit enables the system to deliver more power compared to the bypass diode method. The concept is evaluated using Matlab-Simulink simulation and proven using an experimental test rig. The performance of the proposed circuit is compared with (1) PV system with bypass diode and (2) micro-inverter. The results show marked improvement in the efficiency, especially under heavy partial shading condition.